Australian Women’s and Men’s Incomes by Age of Youngest Child - Grace , Marty (Journal of Law and Governance, 2007)
Responsibility for children impacts on women’s and men’s paid and unpaid work. Paid and unpaid work impact on each other. Aiming to ‘allow men and women to care equally for their families’ frames the issue as one of gender equality. While this is valid, sharing responsibility for children is also a matter of equity between parents and non-parents. The unpaid work of caring for children is an economic input, and the person who contributes this work is likely to suffer the consequences of reduced labour market earning. In Australia, there is some recognition of these matters, with government assistance to most families with the costs of raising children. As we develop a better understanding of how the work of caring for young children restricts parents’ ability to earn labour market income we will be better placed to develop realistic resourcing models. This study presents a new way of looking at income data and highlights the need for further research into incomes following childbearing and the way that incomes vary between women and men, and with the age of the youngest child.